Fit Accuracy of Complete Denture Base Fabricated by CAD/CAM Milling and 3D-Printing Methods - Charoenphol, Kanyakorn; Peampring, Chaimongkon (European Journal of Dentistry, 2022)
Objective Digital complete denture fabrication can be accomplished by either milling or three-dimensional (3D)-printing approach in which minimal distortion during processing contributes to effective denture base adaption, which leads to good denture retention. The purpose of this study was to compare the fit accuracy of milled and 3D-printed complete denture bases.Materials and Methods The reference edentulous maxillary arch model was scanned to generate virtual denture bases using computer-aided manufacturing software that exports as standard tessellation language files. Denture bases were constructed using a milling and 3D-printing technique using digital light processing method (n = 10). Intaglio surfaces of denture bases were scanned and superimposed on the reference model. The fit accuracy was quantified as root mean square error and evaluated statistically using independent t-test comparisons with a significance level of 0.05.Results Milled denture bases were significantly more accurate in adaptation than 3D-printed dentures in the overall intaglio area and primary bearing area of denture bases. 3D-printed denture bases demonstrated significantly greater accuracy in adaptation than milled denture bases in the peripheral/posterior palatal seal area.Conclusion Milled denture bases fit better in the overall and primary stress-bearing areas than 3D-printed dentures, while 3D-printed dentures appeared more accurate in the peripheral seal area, which had a minor undercut that is not suitable for using milling technology.
Keywords: denture; three-dimensional printing; computer-aided design